2017
DOI: 10.1111/ejn.13704
|View full text |Cite
|
Sign up to set email alerts
|

Three shades of grey: detecting brain abnormalities in children with autism using source‐, voxel‐ and surface‐based morphometry

Abstract: Autistic spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social interactions, communication and stereotyped behaviour. Recent evidence from neuroimaging supports the hypothesis that ASD deficits in adults may be related to abnormalities in a specific frontal-temporal network [Autism-specific Structural Network (ASN)]. To see whether these results extend to younger children and to better characterize these abnormalities, we applied three morphometric methods on brain grey m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 50 publications
(76 reference statements)
3
45
0
Order By: Relevance
“…Furthermore, alterations in the frontal lobe are consistent with the known role of frontal striatal circuitry with repetitive behaviours (Kohls et al, 2014), making it a potentially useful endophenotype of these symptoms. A further nine studies reported CT changes in the temporal lobes, however the direction of these findings was inconsistent with four reporting regional increases in temporal lobe CT (Andrews et al, 2017; Haar et al, 2016; Hyde et al, 2009; Sharda et al, 2016b), and five reporting regional decreases in temporal lobe CT (Andrews et al, 2017; Doyle‐Thomas et al, 2013a; Ecker et al, 2013a; Pappaianni et al, 2018; Shi et al, 2013). As with the temporal lobe, the remaining findings showed a comparable number of studies reporting increases and decreases in the CT of other brain regions.…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, alterations in the frontal lobe are consistent with the known role of frontal striatal circuitry with repetitive behaviours (Kohls et al, 2014), making it a potentially useful endophenotype of these symptoms. A further nine studies reported CT changes in the temporal lobes, however the direction of these findings was inconsistent with four reporting regional increases in temporal lobe CT (Andrews et al, 2017; Haar et al, 2016; Hyde et al, 2009; Sharda et al, 2016b), and five reporting regional decreases in temporal lobe CT (Andrews et al, 2017; Doyle‐Thomas et al, 2013a; Ecker et al, 2013a; Pappaianni et al, 2018; Shi et al, 2013). As with the temporal lobe, the remaining findings showed a comparable number of studies reporting increases and decreases in the CT of other brain regions.…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%
“…From the reviewed studies outlined in Supplementary Table 1, this increase in ICV is largely a result of regional increases in the grey matter volume (GMV), with 20 studies reporting regional increases in GMV, compared to 10 studies reporting reduced regional GMV. One of the most implicated regions of autism was a reported increase in GMV in the inferior, superior and middle temporal gyri in 13 reviewed studies (Brun et al, 2009; Ecker et al, 2012, 2010b, Lai et al, 2015, 2013; Lim et al, 2015; Pappaianni et al, 2018; Riddle et al, 2017; Wang et al, 2017; Xiao et al, 2014). The involvement of the temporal lobe in autism has been discovered previously (Hetzler and Griffin, 1981), and can be involved with the socioemotional abnormalities that are typical of ASD (Bachevalier, 1994; Blakemore, 2008).…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that study, the sex specific effects were found only for white, not gray matter. Furthermore, abnormal intraparietal sulci (Auzias et al 2014) and reduced gyrification of an area near the intraparietal sulcus (Pappaianni et al 2017) were observed in male children with ASD. Functional activation studies have found differential activation in males with ASD in the intraparietal sulcus during motor learning (Travers et al 2015) response shifting (Shafritz et al 2008) tasks, and in the orbital gyri during motor-inhibition 1 5 (Schmitz et al 2006) and temporal delay decision making (Murphy et al 2017), and these differences correlated in most cases with RRBI symptoms (Shafritz et al 2008;Travers et al 2015;Murphy et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Our authors wade into the ever thorny issue of phenotyping, classification systems and putative relationships between the autism and schizophrenia phenotypes (Aggernaes, ). The issue showcases new work that very effectively leverages the publicly available consortial neuroimaging databases to interrogate potential structural and functional differences between ASD and neurotypical individuals (Pappaianni et al ., ; Subbaraju et al ., ). Structural brain imaging approaches are also used to assess potential white matter tract differences in both the superior longitudinal fasciculus (Fitzgerald et al ., ) and the oft‐implicated corpus callosum (Giuliano et al ., ).…”
mentioning
confidence: 99%